Desenvolvimento de biocompósitos de Poli (ácido láctico)/biocargas para impressão 3d de scaffolds para engenharia de tecidos ósseos - Backes, Eduardo Henrique (2020)
As life expectancy increases worldwide, there is an increased need for orthopedic procedures to repair bone defects resulting from trauma. In this context, new surgical procedures and bone repair materials, such as scaffolds and temporary models for bone regeneration have been developed. In this doctoral dissertation, the development of printable biocomposites composed of poly(lactid acid) (PLA)/bioactive fillers envisioning bone tissue engineering was investigated as an alternative for scaffold fabrication that supports bone growth and could be manufactured to fit the specifics of individuals. During the development of PLA/biofiller composites, an intense investigation was carried out on the processing, rheological and thermal characteristics and molecular properties and their correlation with the characteristics needed for manufacturing and printing filaments with bioactive properties. PLA filaments and PLA/hydroxyapatite (HA) and PLA/b-tricalcium phosphate (TCP) biocomposites were produced by twin screw extrusion, and scaffolds with the biomimetic bone structure were 3Dprinted from the filaments. The scaffolds were characterized by compression tests and presented compressive properties similar to those of human bone. Bioactivity and biocompatibility were analyzed using simulated body fluid and cell line tests, respectively. The scaffolds were able to originate the formation of calcium phosphates within seven days, indicating an adequate environment to support cell growth, and tests with cell lines showed that biocomposite scaffolds are capable of supporting cell growth and differentiation. In summary, PLA/HA and PLA/TCP biocomposite scaffolds with high biocompatibility and bioactivity properties were developed. The use of 3D printing enables the manufacturing of an infinite number of shapes that are suitable to repair bone defects.